Subjectivity, invisibility, experience and identity of High School students in Brazil: State of knowledge (Research, Society and Development, 2025)
Accounting for about one-sixth of Brazil's population, young people have been a recurring concern for academics since the early 21st century. In 2022, 12.7 million individuals aged 15 to 19 were neither studying nor working, with the primary cause of school dropout being a lack of interest in studies. As individuals capable of assigning their own meanings and belonging to a diverse group, it is essential to examine the reasons behind this disengagement. The objective of this work is to examine the pluralities of academic writings on youth, particularly in the school context, discussing the subjectivity, invisibility, experience, and identity of high school students. The reviewed works reveal young people's dissatisfaction with common school practices, such as conservative ideals some teachers tend to propagate, hegemony, lack of recognition of the different social classes’ students belong to, and their consideration in activities and evaluations. Some young people report attending high school only out of obligation or to facilitate entering the job market, with no desire to pursue further academic life due to the expectation that negative experiences will persist. The study emphasizes the urgent need for changes in schools' modus operandi and the adoption of more inclusive, democratic, and youth-sensitive practices.